Coding Interviews Questions, Analysis & Solutions - He, Harry; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
This book is about coding interview question of software and Internet companies. It covers five key factors which determine performance of candidates: (1) the basics of programming languages, data structures and algorithms, (2) approaches to writing code with high quality, (3) tips to solve difficult problems, (4) methods to optimize code, (5) soft skills required in interviews. The basics of languages, algorithms and data structures are discussed as well as questions that explore how to write robust solutions after breaking down problems into manageable pieces. It also includes examples to focus on modeling and creative problem solving. Interview questions from the most popular companies in the IT industry are taken as examples to illustrate the five factors above. Besides solutions, it contains detailed analysis, how interviewers evaluate solutions, as well as why they like or dislike them. Readers will improve their interview performance after reading this book. It will be beneficial for them even after they get offers, because its topics, such as approaches to analyzing difficult problems, writing robust code and optimizing, are all essential for high-performing coders.
Keywords: Computer science; Information systems; Computer Science; Programming Languages, Compilers, Interpreters; Information Systems and Communication Service